Quality Standards for Pollution Prevention Countermeasures for Safety and Security at the Port of Surabaya (Survey o (Survey on Tanker Ships at the Port of Surabaya) - Sutralinda, Dety (Publisher Cv. Inara, 2024)
The purpose of this study is to determine and analyze the activities of the shipping fleet in the use and use of aids to prevent and prevent pollution of the marine environment, the attention and willingness of officers and crew on the prevention and prevention of pollution of the marine environment, as well as strategies for handling and preventing pollution of the marine environment to support safety and shipping security. By using descriptive qualitative research, data collection is done through interviews and documentation studies to be further processed and analyzed. The results of the first analysis showed that there were still ships that were not in accordance with international standards on the means of supporting marine pollution prevention equipment and there were still crew members who were not aware of the need to prevent sea pollution. The second analysis shows that the attention and willingness of the ship's officers and crew still aboard the ship's officers who neglected the prevention of pollution by ships, not all crew members have the habit of paying attention to pollution by ships. The results of the third analysis indicate that there are still shipping companies that have not yet fully equipped the pollution prevention aids on ships, when shipping equipment is damaged it is rather difficult to provide a replacement. The results of the fourth analysis show that the strategy for preventing and preventing pollution of the marine environment to support shipping safety and security is the result of an analysis of the strengths and weaknesses as well as opportunities and threats to increase the prevention and prevention of pollution of the marine environment to support shipping safety and security.